Comparative Study on Effect of Rabeprazole Versus Omeprazole in Acid-peptic Disorder with Helicobacter pylori Infection - Gurung, Sukh Bahadur; KC, Shiva Raj; Gyawali, Purnima; Amatya, Gyanendra Lal (Journal of Nepal Health Research Council, 2020)
Background: Gastritis is one of the common diseases, which is frequently caused by Helicobacter pylori. Triple therapy has resulted significant decrease in morbidity and complications. Newer proton pump inhibitor drug rabeprazole has been introduced in the market. The aim of this study is to compare its efficacy with omeprazole in triple therapy regimen.Methods: A total of 100 patients who were positive for Helicobacter pylori and gave consent in participating in the study were included. Fifty patients were prescribed omeprazole-based triple therapy and other 50 were prescribed with rabeprazole-based triple therapy. After 2 weeks of triple therapy and 4 weeks of proton pump inhibitor treatment, Helicobacter pylori antigen was tested in faecal material. Results: Out of 100 patients, there was significant correlation between epigastric pain, nausea and water brash with p value, 0.001. Similarly P-value was < 0.001 among hiatus hernia and reflux whereas p value was < 0.05 between bile reflux, hiatus hernia and reflux. In follow up study, after triple therapy, Helicobacter pylori antigen tests were negative in 94% of the study population, who were prescribed rabeprazole which was similar who were prescribed omeprazole (92%).Conclusions: Rabeprazole (20 mg) has proved similar Helicobacter pylori eradication rates compared with omeprazole (40 mg) when co-administered with of antibiotics (amoxicillin and clarithromycin) for two weeks.Keywords: Gastritis; heart burn; hyperchlorhydria; proton pump inhibitors; triple therapy.